THE ROLE OF THE FAIR TRIAL PRINCIPLE RESPECTING TO THE HUNGARIAN CONSTITUTIONAL COMPLAINTS - Dr. Czine, Ágnes (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
ABSTRACT Having entered into force of the Hungarian Fundamental Law, a new type of constitutional complaint was created, which allows the Hungarian Constitutional Court to examine constitutional aspects in a specific court proceeding. In practice, however, applicants and their legal representatives try to use this legal institution to review the results of lawsuits that are unfavourable for them from their point of view. The most common ground for this review is Article XXVIII (1) of the Hungarian Fundamental Law that stipulates the principle of fair trial. This study provides an overview about the main features of the new type of constitutional complaint and the partial rights of the right to a fair trial. The author concludes that, if applicants deal with this remedy rightly, it can indeed be an effective and important tool to ensure the constitutionality of court proceedings.